Endovascular treatment with transvenous approach for embolization of carotid cavernous fistula (Medical Journal of Indonesia, 2014)
The aim of endovascular treatment in carotid cavernous fistula is to close the tear side at cavernous sinus part. It can be dealt either by transvenous or transarterial approach. The option is influenced by type of fistula and angioarchitectural findings. We described two different transvenous routes emphasizing on anatomical consideration and its technical aspect.